Electrochemical behaviour of titanium in fluoride-containing saliva - Fernández Lorenzo de Mele, Mónica Alicia (2000)
The effect of fluoride on the electrochemical behaviour of titanium was studied. Open circuit potentials, breakdown potentials (Eb) and potentiostatic transient currents were measured in synthetic salivas of different compositions. Optical and scanning electron microscopic observations were also made. Results show that the growth rate of Ti oxide layer is affected by fluoride anions and tensile stresses are developed. The OCP/time relationship of Ti immersed in salivas A and B obeys a logarithmic law which depends on the saliva composition. The Eb value is influenced by the thickness of the oxide layer, by the composition of the saliva (including fluoride concentration), and by the technique utilised for its evaluation. Thus, results reported in the literature, which seem to be contradictory, could be explained taking into account the experimental conditions assayed. A careful control of the titanium-containing dental materials should be made after long treatments with fluoride-containing prophylactic products or when fluoride-releasing restorative materials are present in the vicinity.